SOURCES AND FATE OF AMINO SUGARS IN COASTAL PERUVIAN SEDIMENTS - Niggemann J.; Schubert C.J. (My University, 2006)
Amino sugars are involved in the marine carbon and nitrogen cycles and comprise a geochemically significant fraction of marine organic material (OM). However, information on abundance and distribution of these compounds in marine sediments is scarce. Three sediment cores (<50 cm) from the coastal region off Peru were investigated for concentrations of glucosamine (GlcN), galactosamine (GalN), mannosamine (ManN), and muramic acid (Mur). The sum of the four amino sugars accounted for 1.0-2.4% of organic carbon and 1.9-3.8% of nitrogen in the sediments. At the shallowest (102 m) and the deepest site (1278 m), carbon-normalized concentrations decreased down-core, suggesting preferential degradation of amino sugars compared to bulk sedimentary OM. At the site from the center of the oxygen minimum zone (238 m), amino sugar concentrations were high throughout the core, pointing to enhanced preservation of amino sugars under anoxic conditions. GlcN (44-56 mol%) and GalN (33-42 mol%) were the dominant amino sugars in all investigated samples, while ManN (6-14 mol%) and Mur (1-4 mol%) were significantly less abundant. Mur was predominantly associated with cell wall remains rather than with living bacteria, since bacterial abundances estimated based on Mur concentrations were up to 500 times higher than cell counts reported for sediments from this area. GlcN/GalN-ratios (1.1-1.7) indicated that chitin, a polymer of GlcN, was not a major contributor to the amino sugar pool of the investigated sediments. Furthermore, GlcN/Mur-ratios (13-68) are inconsistent with a predominant contribution of intact peptidoglycan, which exhibits a 1:1-ratio. The present study includes a compilation of previously published information on distribution and abundance of amino sugars in the marine environment. Both concentrations and ratios observed in the Peruvian sediments fall in the range of values reported for OM in water column and sediments from different oceanic regions and water depths. Although specific sources for the majority of sedimentary amino sugars remain unidentified, there are indications for a major prokaryotic origin. As suggested in previous studies, the uniform amino sugar compositions of altered marine OM and particularly the close association of GlcN and GalN, which is similar to the ratio observed in living bacteria, are consistent with a transformation of planktonic into bacterial OM. ? 2006 Elsevier Inc. All rights reserved.
Keywords: CARBON CYCLE; CHITIN; COASTAL SEDIMENT; NITROGEN CYCLE; WATER COLUMN